2020
DOI: 10.1002/jso.26289
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of carcinoma ex pleomorphic adenoma compared to de novo adenocarcinoma of major salivary glands

Abstract: Background and ObjectivesCarcinoma ex pleomorphic adenoma (CXPA) is a rare disease of the major salivary glands that remains poorly characterized. Our objective was to compare the clinical outcomes of patients with CXPA of the major salivary glands to those with de novo adenocarcinomas.MethodsReview of the NCDB between 2004 and 2016 to compare cases of CXPA and adenocarcinoma of major salivary glands. Demographics, clinical characteristics, and survival were analyzed.ResultsWe identified 1181 patients with CXP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
(58 reference statements)
1
5
1
Order By: Relevance
“…The OS of CPA indicates a relatively good prognosis. The presented results are better than in other studies (range 25–68.5%) [ 33 , 51 , 53 , 54 , 71 , 72 ], but worse than in the study of Zbären et al [ 79 ] who noted 5-year OS of 76%.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The OS of CPA indicates a relatively good prognosis. The presented results are better than in other studies (range 25–68.5%) [ 33 , 51 , 53 , 54 , 71 , 72 ], but worse than in the study of Zbären et al [ 79 ] who noted 5-year OS of 76%.…”
Section: Discussioncontrasting
confidence: 86%
“…Poor prognosis concerns patients with adenocarcinoma, which was confirmed by other studies; 5-year OS was estimated at 43–62.2% [ 43 , 58 , 59 , 60 , 72 ]; and 10-year OS was only 20.7% [ 58 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although false positivity is common (rate of 68.9%), it should not be ignored, and our findings showed that lymph node enlargement was significantly related to MT, which was also confirmed by Seok et al 7 . The value of CT in detecting lymph node metastasis in head and neck squamous cell carcinoma has been widely evaluated 20 . The classic feature is cystic changes within the lymph node; however, there might be different manifestations from lymph node metastasis in salivary malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…4 Aging, tumor volume, radiation experience, and tumor recurrence are all possible causes of malignant transformation. 5 Adenocarcinoma, adenoid cystic carcinoma, apocrine carcinoma, myoepithelial carcinoma, and mucoepidermoid carcinoma are among the different histopathological subgroups of Ca ex PA. Ca ex PA with the histologic subtype mucoepidermoid carcinoma is extremely uncommon. 6 The majority of patients could be managed with eye-sparing surgery and radiation therapy.…”
mentioning
confidence: 99%